Game Changers in Management [całość] - Hajdas, Monika. Redaktor (Publishing House of Wroclaw University of Economics and Business, 2023)
[A “game changer” is a metaphor commonly used to describe a broad range of events and phenomena in different fields and domains, from natural disasters, through economic crises, emerging narratives, technological or social innovations to conflicts and political or military interventions. Although precise definitions of a “game changer” vary and its conceptual boundaries remain blurred scholars agree that its main quality is the ability to change the status quo. Management scholars have long been interested in increasing the relevance and impact of their studies by addressing a diverse range of global issues. This aspiration to offer significant and meaningful theoretical, practical and societal contributions has led to the advent of strand of management research related to “grand challenges”. Solving any of these challenges could be a game changer, not only from management studies perspective but also from a wider social standpoint. The monograph on Game Changers in Management includes eight chapters that draw inspiration from a diverse set of theories – such as technology adoption, service-dominant logic or information systems (IS) success model, and industrial contexts – from military, through board games to higher education. In the monograph authors discuss current challenges in management research and practice and offer their valuable insights into advancing the knowledge on how to tackle those challenges.] z zapowiedzi
s. 131
Keywords: Sustainable Development Goals; artificial intelligence; Industry 5.0; organisational resilience; ERP; crowdfunding; development centres; student experience